Ultrastructural aspects of oogenesis and oocyte primary growth in Serrasalmus spilopleura (Teleostei, Characiformes, Characidae) - Guimaraes, ACD; Quagio-Grassiotto, I (Churchill Livingstone, 2001)
The ultrastructural characteristics of the organelles present in Serrasalmus spilopleura oogonia and oocytes undergoing primary growth were described in detail, considering its role in the nuclear and cytoplasmic metabolic processes that occur in these cell types. Even though these cells do not significantly differ from those similar to them that are found in other teleost groups, the analysis of their ultrastructure makes available new data on the reproductive biology of Characiformes. (C) 2001 Harcourt Publishers Ltd.
Keywords: ultrastructure; fish; oogonia; oocyte; Serrasalmus spiloleura